Pengaruh Health Education Dengan Media Audiovisual Terhadap Pengetahuan Sadari Pada Remaja Putri di MTsN 3 Jombang - Maysaro; Erna Ts; Fitriyah; Faishol Roni; Dina Camelia; Leo Yosdimyati (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract Adolescence in adolescence starting from the age of 11-14 years is characterized by hormonal and physical changes, especially breast growth. Abnormalities that may occur in the breast such as cancer, mammoth CA, tumors and others. Breast cancer has the highest mortality rate, because it is too late to detect early in adolescents. The efforts of young women must have good knowledge, especially reproductive health (SADARI), with education using audiovisual media that can make it easier to convey health information.The purpose of this study is to find out the influence of health education on SADARI knowledge in adolescent girls in MTsN 3 Jombang. The design and method of this research are in the form of a pre-experiment using the one-group pre-post test desaign approach. The sampling technique used a total sampling of 39 respondents. The measuring tool that SAP uses and the knowledge questionnaire about SADARI. The statistical test in this study uses the Wilcoxon Sign Rank Test.The results of the statistical test using the Wilcoxon Sign Rank Test at SPSS with a sig value of 0.000<0.05 H1 were accepted, which means that there is an Influence of Health Education on SADARI Knowledge in Adolescent Girls in MTsN 3 Jombang. Conclusions and Suggestions from the results of this study show that there is an Influence of Health Education on SADARI Knowledge in Adolescent Girls in MTsN 3 Jombang It is hoped that future researchers if they want to research about SADARI in adolescents can use the latest motivation or ideas. Keywords : Health Education, audiovisual method, SADARI, Young Women